STEM-24. RADIATION-INDUCED EXTRACELLULAR VESICLE (EV) RELEASE OF miR-603 PROMOTES IGF1-MEDIATED STEM CALL STATE IN GLIOBLASTOMAS. (9th November 2020) - Ramakrishnan, Valya; Xu, Beibei; Akers, Johnny; Nguyen, Thien; Ma, Jun; Dhawan, Sanjay; Ning, Jianfang; Mao, Ying; Hua, Wei; Kokkoli, Efrosini; Furnari, Frank; Carter, Bob; et al.
Abstract: INTRODUCTION: Release of exosomes and extracellular vesicles (EV) by glioblastomas plays key roles in modulating the tumor microenvironment and therapeutic response. Studies to date have largely focused on the impact of EV and exosomes on the recipient cell. Here, we demonstrate that EV-mediated export of a master-regulatory miRNA has fate-determining impacts on the cell releasing the EVs. METHODS: microRNA (miRNA) profiling was performed using clinical glioblastoma specimens from the same patients derived pre- and post-standard of care treatment. Mechanism mediating altered miRNA homeostasis were assessed. RESULTS: While the levels of nearly all miRNAs remained unchanged after standard-of-care treatment, decreased levels of few, select miRNAs were observed, including miR-603. In response to ionizing radiation (IR), but not temozolomide (TMZ), glioblastoma cell lines exhibited a time-dependent decrease in miR-603 levels. While miR-603 biogenesis and degradation remained unchanged after IR, IR induced an increase in EV-mediated export of miR-603. Profiling of miR-603 targets revealed that miR-603 repressed the insulin-like growth factor 1 (IGF1) and IGF1 receptor (IGF1R), genes required to maintain the cancer stem cell (CSC) state, as well as MGMT, the gene encoding a DNA repair protein that detoxifies temozolomide (TMZ) induced DNA damages. IR induced export of miR-603 de-repress IGF1/IGF1R to promote radiation resistance and de-repress MGMT to promote cross-resistance to TMZ and CCNU. Ectopic miR-603 expression overwhelmed cellular capacity for miR-603 export and synergized with the tumoricidal effects of IR and temozolomide (TMZ). CONCLUSIONS: Radiation stimulated EV-mediated export of miR-603 to facilitate acquired resistance to IR and cross-resistance to DNA alkylating agents.